Commissioning care for people with dementia at the end of life: a mixed-methods study. Issue 12 (21st December 2016) - Gotts, Zoe M; Baur, Nicole; McLellan, Emma; Goodman, Claire; Robinson, Louise; Lee, Richard P
Abstract : Objectives: To understand how end-of-life (EoL) care for people with dementia is currently commissioned (ie, contracted) and organised, with a view to informing the development of commissioning guidance for good-quality community-based EoL care in dementia. Design: Mixed-methods study; narrative review and qualitative interviews. Setting: 8 National Health Service (NHS) clinical commissioning groups (CCGs) and five adult services across England. Methods: Narrative review of evidence; 20 semistructured interviews (telephone and face-to-face) with professionals involved in commissioning EoL care for people with dementia. Main outcome measures: Summary of the existing evidence base for commissioning, commissioners' approaches to the commissioning process for EoL care for people with dementia in England. Results: In the context of commissioning EoL for people with dementia, the literature review generated three key themes: (1) importance of joint commissioning; (2) lack of clarity for the process and (3) factors influencing commissioning. In exploring health professionals' perceptions of the commissioning process, 'uncertainty' was elicited as an overarching theme across the CCGs interviewed. Organisation of the process, lack of expertise, issues surrounding integration and the art of specification were considered important factors that contribute to the uncertainty surrounding the commissioning process. Conclusions: The current evidence base for commissioning EoL care is limited with considerable uncertainty as how clinical commissioners in England undertake the process to ensure future services are evidence-based.